The Impact of Social and Ecological Accounting in Forest Management - Nia Nafilah Andani; Wahyuni Wahyuni; Nilawati Nilawati; Isnaini Ridwan (Jurnal Impresi Indonesia, 2024)
This study examines the impact of social and ecological accounting in forest management, given the importance of management practices that consider not only economic aspects but also social and environmental sustainability. The research used qualitative methods with a case study approach and literature review. Data was collected through direct observation, interviews with stakeholders, and analysis of documents such as sustainability reports and forest management policies. The results show that the integration of social and ecological accounting in forest management policies can improve transparency, accountability and sustainability of forest management. This practice helps in identifying social and environmental impacts more comprehensively. The findings confirm the importance of implementing social and ecological accounting to create more environmentally responsible policies and forest communities. This research also shows that the involvement of local communities in forest management can improve the effectiveness of forest management and conservation. This research makes an important contribution to the development of sustainable forest management strategies by emphasizing the importance of social and ecological dimensions in forest management accounting.